OpenMRS FRAMEWORK : HEALTH INFORMATION SYSTEM SOLUTION TO DEVELOP IN SABHA, LIBYA - Abobaker, Mostafa; Sulistyo, Selo; Permanasari, Adhistya Erna (Universitas Respati Yogyakarta, 2014)
The health care system in Libya in recent years does not change significantly, less developed and modernized. This problem is further exacerbated by the revolution that occurred in Libya. The revolution that occurred in 2011 has caused the health care system into collapse. In this study conducted a review for the development of health information systems in Libya by using OpenMRS Framework.At the stage of gathering information using questionnaires concluded that the majority of respondents (about 95.35%) wanted the development of a new system that can resolve the main problems that occurred in Libya, the health information system ineffective and inefficient in which this system has led to wastage of time and increased operating costs. Based on analysis of system vulnerabilities using PIECES method could also be concluded that the current system is not used effectively and efficiently. In this study is also presented on how to implement OpenMRS.Based on the results of the discussion it can be concluded that OpenMRS is a solution that can be taken for the development of a health information system that is fast, low cost, and is an open source application that only requires a little setting in the system of patient management and care. OpenMRS can be implemented to support the health services of a small clinic to the health services with enterprise scale. Therefore, OpenMRS could be the answer to the development of health information systems in various countries around the world, including Libya.